Contemporary problems of architecture and construction : proceedings of the 12th International Conference on Contemporary Problems of Architecture and Construction (ICCPAC 2020) November 25-26, 2020, Saint Petersburg, Russia - International Conference on Contemporary Problems of Architecture and Construction 2020 : Saint Petersburg, Russia); Evgeny, Rybnov; Akimov, Pavel; Khalvashi, Merab; Eghiazar, Vardanyan (Boca Raton : CRC Press, 2021)
Contemporary Problems of Architecture and Construction 2020 includes contributions on various complex issues and aspects of engineering and construction of buildings and structures, protection, reconstruction and restoration of architecture, as well as intellectualization of energy and safety systems functioning urban development. The contributions were presented at the eponymous conference (ICCPAC 2020, St Petersburg, Russia, November 25-26, 2020), and cover a wide range of topics: Urban development: problems of urban construction and architecture Engineering, construction and operation of buildings and structures Implementation of building information modeling (BIM) and geo-information systems (GIS) technologies in the construction industry Energy efficiency of buildings and maintenance systems Engineering technologies of sustainable nature management and environmental protection Intellectualization and algorithmization of large cities road safety systems functioning Economics and management in construction and public utility services. Contemporary Problems of Architecture and Construction 2020 will be of interest to academics and professionals involved in the urban development, engineering technologies, architecture and construction, economics and management in construction industry.
"Balkema book"
Conference proceedings.
OCLC-licensed vendor bibliographic record.
Keywords: Architecture -- Congresses; Buildings -- Congresses; Construction industry -- Congresses; TECHNOLOGY / Engineering / Civil